A biocompatible superparamagnetic chitosan-based nanoplatform enabling targeted SN-38 delivery for colorectal cancer therapy. (15th November 2021) - Wu, Danjun; Li, Yi; Zhu, Lixi; Zhang, Wangyang; Xu, Shumin; Yang, Yan; Yan, Qinying; Yang, Gensheng
Abstract: 7-Ethyl-10-hydroxycamptothecin (SN-38) as a potent anti-tumor candidate, suffers the constraints from its poor water solubility, pH-dependent lactone ring stability and the lack of efficient delivery system without losing its activity. Herein, biocompatible superparamagnetic chitosan-based nanocomplexes complexing with water-soluble polymeric prodrug poly(L-glutamic acid)-SN-38 (PGA-SN-38) was engineered for efficient delivery of SN-38. The manufacturing process of colloidal complexes was green, expeditious and facile, with one-shot addition of PGA-SN-38 into chitosan solution without using any organic solvent or surfactant. Upon introducing ultra-small-size superparamagnetic nanoparticles (~10 nm), the developed magnetic nanocomplexes exhibited significantly boosted tumor-targeted accumulation and efficient cellular internalization under a local magnetic field. Notably, the magnetic nanocomplexes achieved distinctly superior targeting and anti-tumor efficacy in the established xenograft colorectal cancer model of mice, with high tumor suppression rate up to 81%. Therefore, this superparamagnetic chitosan-based nanocomplex system could provide a promising platform for the targeted delivery of SN-38 in colorectal cancer therapy. Highlights: Green synthesis of nanocomplexes without using any organic solvent or surfactant Favorable colloidal stability in the simulated physiological conditions Hydrophilicity increasement of SN-38 and sustained drug release from nanocomplexes Significant enhancement on tumor-targeting ability by magnetic nanocomplexes Superior anti-tumor efficacy and reduced systematic toxicity of the nanocomplexes